Workers' Mobility and Internal Labour Markets - Carneiro, Anabela (2010)
Understanding factors that influence mobility is relevant and has benefits for both organizations and individuals. In this study, we propose a different outlook on internal mobility and on the internal working of the firm. Instead of focusing on the determinants of mobility and promotions within the same establishment, we will focus on internal mobility that involves an establishment change. On the other hand, we will focus on the outcomes of mobility but, our approach, will allow us to quantify and distinguish between different returns to different types of mobility. To understand the determinants of mobility and to identify the respective returns we will organize mobility into the following classification: Same-employer transfers without region change; Same-employer transfers with region change; Employer changes without region change; Employer changes with region change; and our base category, employees that remain in the same establishment of the same firm. The dataset in this study comes from Quadros de Pessoal (QP), a matched employer-employee survey. Our results indicate that same-employer transfers include workers that are performing well at the present .rm. These transfers may act as a "promotion" within the firm which is consistent with our hypothesis that in multi-plant firms there exists a global internal labour market which is built on the firm as a whole. Comparing wage premiums for the group of same-employer transfers involving region changes with the group of same-employer transfers that were locally transferred, we propose a new approach to estimate wage premiums for migration. We conclude that there exists a greater reward when employees have to incur in additional costs such as those involved in relocation.